Orthogonal dual reporter-based gain-of-signal assay for probing SARS-CoV-2 3CL protease activity in living cells: inhibitor identification and mutation investigation - Zhu-Chun Bei; Huanhuan Yu; Hong Wang; Qingyun Li; Baogang Wang; Dongna Zhang; Likun Xu; Liangliang Zhao; Shuwei Dong; Yabin Song (Emerging Microbes and Infections)
The main protease (3-chymotrypsin-like protease, 3CLpro) of SARS-CoV-2 has become a focus of anti-coronavirus research. Despite efforts, drug development targeting 3CLpro has been hampered by limitations in the currently available activity assays. Additionally, the emergence of 3CLpro mutations in circulating SARS-CoV-2 variants has raised concerns about potential resistance. Both emphasize the need for a more reliable, sensitive, and facile 3CLpro assay. Here, we report an orthogonal dual reporter-based gain-of-signal assay for measuring 3CLpro activity in living cells. It builds on the finding that 3CLpro induces cytotoxicity and reporter expression suppression, which can be rescued by its inhibitor or mutation. This assay circumvents most limitations in previously reported assays, especially false positives caused by nonspecific compounds and signal interference from test compounds. It is also convenient and robust for high throughput screening of compounds and comparing the drug susceptibilities of mutants. Using this assay, we screened 1789 compounds, including natural products and protease inhibitors, with 45 compounds that have been reported to inhibit SARS-CoV-2 3CLpro among them. Except for the approved drug PF-07321332, only five of these inhibit 3CLpro in our assays: GC376; PF-00835231; S-217622; Boceprevir; and Z-FA-FMK. The susceptibilities of seven 3CLpro mutants prevalent in circulating variants to PF-07321332, S-217622, and GC376 were also assessed. Three mutants were identified as being less susceptible to PF-07321322 (P132H) and S-217622 (G15S, T21I). This assay should greatly facilitate the development of novel 3CLpro-targeted drugs and the monitoring of the susceptibility of emerging SARS-CoV-2 variants to 3CLpro inhibitors.